2021
DOI: 10.1186/s12870-021-02923-9
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the 14-3-3 gene family in cotton flowering

Abstract: Background In plants, 14-3-3 proteins, also called GENERAL REGULATORY FACTORs (GRFs), encoded by a large multigene family, are involved in protein–protein interactions and play crucial roles in various physiological processes. No genome-wide analysis of the GRF gene family has been performed in cotton, and their functions in flowering are largely unknown. Results In this study, 17, 17, 31, and 17 GRF genes were identified in Gossypium herbaceum, G.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 72 publications
(124 reference statements)
3
16
0
Order By: Relevance
“…Gh AGAMOUS-LIKE 8-1/-2 ( GhAGL8-1/-2 ), the homologs of APETALA1 ( AP1 ) in cotton, regulate plant height and early maturity of cotton ( Su et al, 2018 ). GENERAL REGULATORY FACTORs (GRFs) play important roles in flowering regulation and meristem development ( Sang et al, 2021 ). We found that the expressions of GhAGL8-1/2 and GhGRF6 were downregulated in both TRV2:GhMCTP7/12/17 and TRV2:GhKNAT1/2 , suggesting the delayed determination of floral meristem identity ( Figures 9A , B ).…”
Section: Resultsmentioning
confidence: 99%
“…Gh AGAMOUS-LIKE 8-1/-2 ( GhAGL8-1/-2 ), the homologs of APETALA1 ( AP1 ) in cotton, regulate plant height and early maturity of cotton ( Su et al, 2018 ). GENERAL REGULATORY FACTORs (GRFs) play important roles in flowering regulation and meristem development ( Sang et al, 2021 ). We found that the expressions of GhAGL8-1/2 and GhGRF6 were downregulated in both TRV2:GhMCTP7/12/17 and TRV2:GhKNAT1/2 , suggesting the delayed determination of floral meristem identity ( Figures 9A , B ).…”
Section: Resultsmentioning
confidence: 99%
“…The FAC model reveals the functional conservation of florigen complex, because the three proteins constituting FAC are very conserved in seed plants ( Karlgren et al, 2011 ; Taoka et al, 2011 ). Through genome-wide identification and analysis, we found that there were five FD s and 31 14-3-3 homoeologous gene pairs in G. hirsutum ( Liu et al, 2021 ; Sang et al, 2021 ). GhFT–Gh14-3-3–GhFD1/2 complexes can activate the expression of GhAP1 ,the homologous flower identity gene in cotton, thus promoting the flowering.…”
Section: Functions Of Flowering Locus T/single Flower Truss Genes In ...mentioning
confidence: 99%
“…In contrast, GhFT–Gh14-3-3–GhFD3/4/5 complexes in roots activate the expression of AUXIN RESPONSE FACTOR 19 , thereby promoting lateral root development ( Liu et al, 2021 ). The function of FAC in cotton is also influenced by its component 14-3-3 protein, which can either promote or inhibit flowering by regulating the expression of GhAP1 and GhSOC1 ( Sang et al, 2021 ). These studies show that although there is only one FT/SFT protein in polyploid upland cotton, it possesses diverse FD and 14-3-3 proteins available allowing the formation of diversified FACs to regulate different development processes.…”
Section: Functions Of Flowering Locus T/single Flower Truss Genes In ...mentioning
confidence: 99%
“…However, CRISPR/Cas can be a way to overcome this challenge. Recently, Gh14-3-3d genes (involved in stress response) were selected as a target for the improvement in biotic stress response, and this gene was disrupted by CRISPR knockout strategy. Results showed that edited plants presented tolerance to Verticillium dahliae …”
Section: Crispr/cas Applied To Bypass Biotic Stress In Plantsmentioning
confidence: 99%